The distinctive responses of hyperthermophilic, thermophilic and mesophilic anaerobic digesters to restaurant-discharged oily waste. (July 2021) - Wu, Li-Jie; Li, Xiao-Xiao; Yang, Fan; Zhou, Quan; Ren, Rui-Peng; Lyu, Yong-Kang
Graphical abstract: Highlights: Hyperthermophilic methanogenesis hardly occurred for de-oiled grease trap waste. Mesophilic digester could endure the highest loading for single lipid-rich waste. Limit of long chain fatty acids for hyperthermophilic digestion was 5.6 mmol L −1 . Food waste with composite fractions favored conversion of linoleic and oleic acids. Abstract: De-oiled grease trap waste (GTW) has been proven appropriate for anaerobic digestion treatment. Continuous hyperthermophilic at 70 ℃, thermophilic and mesophilic digestion were operated in parallel to investigate the distinctive responses to the de-oiled GTW. Mesophilic digestion achieved higher tolerance loading than the others. Biogas production was detected in the recovery period for the inhibited hyperthermophilic digester, and the recovery time lasted approximately 10 days longer than the thermophilic one. The long chain fatty acid (LCFA) concentrations at the starting points of recovery were determined to be 5.6 mmol L −1 and 6.2 mmol L −1 for the hyperthermophilic and thermophilic digestion, respectively. Under the similar lipid loading, food waste with composite fractions was observed favorable for biogas production in the hyperthermophilic digester. Residual lipid concentration remained higher for the hyperthermophilic digestion, about twice more than the others. Furthermore, composite substrate alleviated the inhibition from LCFAs, for the dominant was converted to the ones with shorter chain length.